Pengaruh Lingkungan Kerja Fisik Dan Budaya Kerja Terhadap Kinerja Karyawan Pt Umara Cipta Rasa Jakarta Selatan - Ahmad Rezeqi Sapril Ridho; Bachtiar Arifudin Husain (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this research is to determine the effect of the physical work environment and work culture on the performance of employees at PT Umara Cipta Rasa. The method used is a quantitative research type with an associative approach. The sampling technique employed is saturated sampling, resulting in a sample of 53 respondents. Data analysis includes validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficients, determination coefficients, and hypothesis testing. The results of this study indicate that the physical work environment has a significant effect on employee performance, with the regression equation Y = 19.604 + 0.566 X1. The hypothesis test shows that the calculated t value is greater than the table t value (8.826 > 2.00856).Thus H0 is rejected and H1 is accepted. Organizational culture has a significant effect on employee performance with the regression equation Y = 10,300 + 0,751 X2 work environment and organizational culture simultaneously have a significant effect on employee performance with the regression equation Y = 8,946 + 0,363 X1 + 0,446 X2. Hypothesis testing obtained a calculated F value > Ftable or (67,707 > 3,18). Thus, H0 is rejected and H3 is accepted. From the results above, the suggestion is to further improve all aspects of the physical work environment, and especially the Work Culture, in this case the company must improve aspects related to self-awareness, aggressiveness, personality, performance and team orientation so that performance is achieved can be maximized.